The nexus between prices, employment and output growth: a global and national evidence - Caporale, Guglielmo Maria; Škare, Marinko (Journal of Business Economics and Management, 2014)
This paper investigates how output growth, employment growth and inflation influence each other in the short/long run. It builds on Phillips (1962) and Blanchard Fischer (1989) assessment that empirical links between output, employment and prices are central issue in modern macroeconomics. This paper brings a global perspective on short and long term links between employment growth, inflation and output growth using panel cointegration framework with non-stationary heterogeneous panel (119 countries over 1970–2010). The empirical results (on global and national level) strongly support the existence of a long-run equilibrium relationship between output growth, employment growth and inflation. A central finding is that possible trade-off effects between growth, employment and prices varies significantly among economies. Therefore, universal answers to questions Is inflation good for growth or Is there a trade-off between employment and growth are not straightforward for general macroeconomic theory. Each country must design own economic policy (targeting) taking into account the quantitative relationships between growth, employment and prices. This has important policy implications also for price setting policies, cost management, market strategy and risk management through productivity-demand disturbances effects on the business environment.